Firm Value Model in Pharmaceutical Companies - Erion; Lili Purnama Sita; Yuli Zain (International Journal of Asian Business and Management, 2024)
This study intends to investigate and fill the knowledge vacuum among academics about the issue wherein leverage is not given priority as a risk factor in relation to institutional ownership and the availability of firm liquidity. Furthermore, investors in the capital market do not perceive leverage to be a major factor. This study uses a quantitative methodology, focusing on chemical businesses listed on the Indonesia Stock Exchange (IDX) over a ten-year period. It does this by using a multiple regression analysis method using panel data. Five companies were chosen through the use of a purposive sampling strategy. Through the use of leverage as an intervening variable, the study aims to maximize Firm Value. Two research models are combined into one, with each passing through different phases of testing for model selection, such as the Lagrange Multiplier, Hausman, and Chow tests. The results of the first model show that while liquidity affects leverage, ownership structure has no effect on it. In the second model, liquidity successfully explains the relationship between ownership structure and firm value. Furthermore, the impact on firm value is not mediated by leverage as an intervening variable. It is expected that these results will function as a roadmap for publicly traded corporations seeking to increase their Firm Value